DETERMINAN PROFITABILITAS BANK UMUM DI INDONESIA (Studi Kasus: Bank Kategori BUKU 4) - Purnamasari, Yeni (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
This study aims to analyze the determinant of banking profitability, which is influenced by internal factors and external factors. This study focus on the impact of internal factors (CAR, NPL, and LDR) and external factors (BI rate and money supply) on bank profitability which is proxied by Return on Assets (ROA). The sample used bank category BUKU 4, with period from 2008 to 2017. The method used in this study is Fixed Effect Method (FEM). The empirical result shows that internal factors (NPL and LDR) have a significant effect on ROA, while CAR had no significant effect on ROA. External factors, BI rate and money supply also have a significant effect on ROA.